2002
DOI: 10.1083/jcb.200201127
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase C βII and TGFβRII in ω-3 fatty acid–mediated inhibition of colon carcinogenesis

Abstract: Încreasing evidence demonstrates that protein kinase C βII (PKCβII) promotes colon carcinogenesis. We previously reported that colonic PKCβII is induced during colon carcinogenesis in rodents and humans, and that elevated expression of PKCβII in the colon of transgenic mice enhances colon carcinogenesis. Here, we demonstrate that PKCβII represses transforming growth factor β receptor type II (TGFβRII) expression and reduces sensitivity to TGF-β–mediated growth inhibition in intestinal epithelial cells. Transge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
83
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 71 publications
(87 citation statements)
references
References 22 publications
4
83
0
Order By: Relevance
“…Loss of TGFb responsiveness during colon carcinogenesis has been associated with genetic and epigenetic inactivation of the TGFb type II receptor Parsons et al, 1995), Smad mutations (Riggins et al, 1997), oncogenic activation of K-Ras (Higashidani et al, 2003), and induction of protein kinase C-beta II (Murray et al, 2002). However, the possible role of Evi1 in TGFb signaling in colon cancer is poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Loss of TGFb responsiveness during colon carcinogenesis has been associated with genetic and epigenetic inactivation of the TGFb type II receptor Parsons et al, 1995), Smad mutations (Riggins et al, 1997), oncogenic activation of K-Ras (Higashidani et al, 2003), and induction of protein kinase C-beta II (Murray et al, 2002). However, the possible role of Evi1 in TGFb signaling in colon cancer is poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…We have focused our recent efforts on deciphering the role of specific PKC isozymes in the development of colon cancer (5)(6)(7). We have shown that colon carcinogenesis is accompanied by changes in PKC isozyme expression, including a dramatic increase in the level of PKC␤II expression (5).…”
mentioning
confidence: 99%
“…These animals exhibit hyperproliferation of the colonic epithelium and enhanced susceptibility to carcinogeninduced carcinogenesis (6). We recently characterized the transforming growth factor ␤ receptor type II (TGF-␤RII) as a target for PKC␤II-mediated transcriptional repression in intestinal epithelial cells and in the colonic epithelium of transgenic PKC␤II mice (7). PKC␤II-induced inhibition of TGF-␤RII renders intestinal epithelial cells insensitive to growth inhibition by TGF-␤ and accounts, at least in part, for the colonic hyperproliferation and increased sensitivity to colon carcinogenesis characteristic of transgenic PKC␤II mice (6,7).…”
mentioning
confidence: 99%
See 2 more Smart Citations